METHODS OF FUNCTIONAL EVALUATION OF ORAL MUCOSA STATE IN EXPERIMENTAL PATHOLOGY - Abramova, L.P.; Kalchuk R.О.; Kirichok L.Т. (World of Medicine and Biology, 2013)
Biochemocal parameters reflecting the functional state of oral mucosa were investigated in experiment together with character and degree of their change depending on influence power of unfavourable factors.